2011
DOI: 10.5755/j01.eee.114.8.684
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Performance Evaluation of a PV-Powered Refrigeration System

Abstract: Performance Evaluation of a PV-Powered Refrigeration System // Electronics and Electrical Engineering. -Kaunas: Technologija, 2011. -No. 8(114). -P. 7-10.This paper presents cool-down, and steady state performance of a 76 W direct current operated household refrigerator powered by a photovoltaic (PV) solar panel and a battery bank. Exergy method has been conducted to investigate of the performance of the PV powered household refrigerator. Experiments are conducted with different cooling loads. In use of this t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
12
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 6 publications
1
12
0
Order By: Relevance
“…The results showed that there was no deference in the performance of the air conditioning unit when using the same refrigerant and changing the source of power from mains to solar power. Same results were obtained by: [3][4][5]. This study aimed to reduce the power generated to the limit that production can't succeed to sustain acceptable operation.…”
Section: Introductionmentioning
confidence: 65%
“…The results showed that there was no deference in the performance of the air conditioning unit when using the same refrigerant and changing the source of power from mains to solar power. Same results were obtained by: [3][4][5]. This study aimed to reduce the power generated to the limit that production can't succeed to sustain acceptable operation.…”
Section: Introductionmentioning
confidence: 65%
“…More recent studies have shown the adaptation of commercial refrigerators to work with DCCompressors as shown in [10]. The obtained COPs were similar for AC refrigerators equipped with inverters [11], [9] and those using DC-Compressors [12], [13], [10] being around 1.7 to 2 for temperature differences between ambient and air compartment of around 25°C. The performance monitoring of the whole solar system has been recently described in [14].…”
Section: Introductionmentioning
confidence: 69%
“…Exergy analysis in the field of refrigeration gives the performance of individual components and also provides a better understanding to improve the system performance. 19 Ekren et al 20 performed exergy analysis on a solar-powered DC refrigerator and observed maximum exergy destruction in the compressor, followed by the condenser, evaporator, and capillary tube. Ekren et al 21 carried out the exergy analysis of a DC refrigerator at various compressor speeds.…”
Section: Introductionmentioning
confidence: 99%
“…19 Ekren et al. 20 performed exergy analysis on a solar-powered DC refrigerator and observed maximum exergy destruction in the compressor, followed by the condenser, evaporator, and capillary tube. Ekren et al.…”
Section: Introductionmentioning
confidence: 99%